Genre-Based Approach In Arabic Language Books Of Madrasah Aliyah - Fatimah Azzahra Mutmainah (Ijaz Arabi Journal of Arabic Learning, 2023)
This study aims to discuss high school (MA) Arabic language books and analyze them in light of the Genre-based Approach (GBA) perspective. This learning approach began to draw scholarly attention after issuing the Decree of Minister of Religious Affairs (KMA) No. 183 of 2019 by the Indonesian  Ministry of Religious Affairs concerning the Arabic Language Education (PBA) curriculum. Academic research on GBA and Arabic language education has begun to be widely conducted, such as that of Hasanah (2022), which examined the implementation of Systemic Functional Linguistics' Genre-Based Approach (SFL-GBA) for PBA students at UIN Maulana Malik Ibrahim Malang. Scholars have yet to devote a specific analysis of MA Arabic books using a genre-based approach. This study found that (a) those books encompass only four types of text (descriptive, recount, exposition, and procedure text), far less than those presented in English and Indonesian books; and (b) contain several stages of a genre-based approach, modeling, joint construction, and independent construction, though implicitly stated.